1966
DOI: 10.1128/jb.91.5.2018-2024.1966
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopy of Staphylococcus aureus Cell Wall Lysis

Abstract: A crude suspension of Staphylococcus aureus cell walls (strain Cowan III) in buffer solution was shown by electron microscopy to lyse slightly after 16 hr, probably owing to the action of autolysin. The lysis was considerably faster and more intense after the addition of lysozyme. A remarkable reduction in thickness and rigidity of the cell walls, together with the appearance of many irregular protrusions in their outlines, was observed after 2 hr; after 16 hr, there remained only a few recognizable cell wall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1967
1967
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…These morphological changes in Staphylococcus aureus cells are speculated to be the result of lysozyme triggered autolysis of bacteria which is the generally accepted mechanism of lysozyme action on Staphylococcus aureus cells. 38,39 In conclusion, we have developed a unique multifunctional biomimetic material comprised of SWNT, DNA, and LSZ using LBL assembly. Precise control of both layer thickness and SWNT alignment within each layer was achieved, and the final coatings had robust mechanical properties.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…These morphological changes in Staphylococcus aureus cells are speculated to be the result of lysozyme triggered autolysis of bacteria which is the generally accepted mechanism of lysozyme action on Staphylococcus aureus cells. 38,39 In conclusion, we have developed a unique multifunctional biomimetic material comprised of SWNT, DNA, and LSZ using LBL assembly. Precise control of both layer thickness and SWNT alignment within each layer was achieved, and the final coatings had robust mechanical properties.…”
mentioning
confidence: 96%
“…In contrast, on the uncoated silicon surface the cells remained intact and maintained their cocci structure. These morphological changes in Staphylococcus aureus cells are speculated to be the result of lysozyme triggered autolysis of bacteria which is the generally accepted mechanism of lysozyme action on Staphylococcus aureus cells. , …”
mentioning
confidence: 99%
“…There have been only a few reports of electron microscopic observations of the dissolution of cell walls of gram-positive bacteria by the action of lytic enzymes (2,5,14). Morphological observations of the autolytic dissolution of the cell walls of Streptococcus faecalis ATCC 9790 were of particular interest to us in view of recent reports (11,12) which indicated that the active form of the wall-bound autolysin preferentially acts on the most recently synthesized portion of the wall first.…”
mentioning
confidence: 99%
“…However, nearly no bacteriostatic effect on S. aureus at any concentrations of LAML solution has been demonstrated (data not shown). Virgilio et al . (1966) reported that S. aureus proved resistant to treatment with several lytic agents, even a number of enzymes such as lysozyme, which completely dissolves certain gram‐positive bacteria, but had little or no action on S. aureus cells.…”
Section: Resultsmentioning
confidence: 99%